Canavanine-Induced Decrease in Nitric Oxide Synthesis Alters Activity of Antioxidant System but Does Not Impact S-Nitrosoglutathione Catabolism in Tomato Roots - Staszek, Pawel; Krasuska, Urszula; Otulak-Kozieł, Katarzyna; Fettke, Joerg; Gniazdowska, Agnieszka (Frontiers in Plant Science, 2019)
Canavanine (CAN) is a non-protein amino acid synthesized in legumes. In mammalians, as arginine (Arg) analogue, it is an inhibitor of nitric oxide synthase (NOS) activity. The aim of this study was to investigate the impact of CAN induced nitric oxide (NO) level limitation on the antioxidant system and S-nitrosoglutathione (GSNO) metabolism in roots of tomato seedlings. Treatment with CAN (10 or 50 µM) for 24-72 h led to restriction in root growth. Arg dependent NOS-like activity was almost completely inhibited, demonstrating direct effect of CAN action. CAN increased total antioxidant capacity and the level of sulphydryl groups. Catalase (CAT) and superoxide dismutase (SOD) activity decreased in CAN exposed roots. CAN supplementation resulted in the decrease of transcript levels of genes coding CAT (with the exception of CAT1). Genes coding SOD (except MnSOD and CuSOD) were up-regulated by CAN short treatment, prolonged exposition to 50 µM CAN resulted in down-regulation of FeSOD, CuSOD, SODP-2. Activity of glutathione reductase (GR) dropped down after short-term (10 µM CAN) supplementation, while glutathione peroxidase (GPx) activity was not affected. Transcript levels of GR genes declined in response to CAN. Genes coding GPx were up regulated by 50 µM CAN, while 10 µM CAN down-regulated GSHPx1. Inhibition of NOS-like activity by CAN resulted in lower GSNO accumulation in root tips. Activity of GSNO reductase (GSNOR) was decreased by short-term supplementation with CAN. In contrast, GSNOR protein abundance was higher, while transcript levels were slightly altered in roots exposed to CAN. This is the first report on identification of differentially nitrated proteins in response to supplementation with non-proteinogenic amino acid. Among nitrated proteins differentially modified by CAN, seed storage proteins (after short-term CAN treatment) and components of the cellular redox system (after prolonged CAN supplementation) were identified. The findings demonstrate that due to inhibition of NOS-like activity CAN leads to modification in antioxidant system. Limitation in GSNO level is due to lower NO formation while GSNO catabolism is less affected. We demonstrated that monodehydroascorbate reductase, activity of which is inhibited in roots of CAN treated plants, is the protein preferentially modified by tyrosine nitration.